A Combination of Synchronous and Asynchronous Meetings in Fully-Online Flipped English Classroom - Farida Noor Rohmah (Concept: Journal of Social Humanities and Education, 2022)
Both teachers and students must adjust to the new teaching strategy, despite all limitations and chances in remote learning during the pandemic. To accomplish the learning objectives, educators must create their courses by utilizing the advantages of technology. In order to optimize students' learning potential, several things had to be taken into account when designing such a remote course. In order to address the issue, this study aimed to demonstrate how the English for Academic Reading course in Universitas ‘Aisyiyah Yogyakarta was developed using the ASSURE (Analyze Learners; State Objectives; Select Method, Media, or Materials; Utilize Media or Materials; Require Learners' Participation; Evaluate and Revise) model in the form of fully-online flipped classroom. The data was gathered through observation and library study. The obstacles and opportunities addressed by both educators and students throughout the remote learning practice were analyzed using a qualitative methodology. The course was developed by mixing synchronous and asynchronous class activities after taking the advantages and disadvantages of distance learning into account. The design included independent learning, content explanations, quizzes, class discussion, and collecting student assessment. Students were shown to be more motivated to study when synchronous and asynchronous class activities were used, according to the evaluations.